Factors associated with prolonged procedure time of embolization for trauma patients. Issue 1 (19th March 2022) - Aoki, Makoto; Matsumoto, Shokei; Toyoda, Yukitoshi; Senoo, Satomi; Inoue, Yukio; Yamada, Masaki; Fukada, Takuya; Funabiki, Tomohiro
Abstract : Aim: Limited information exists on the factors associated with prolonged procedural time in embolization for trauma patients. We clarified the clinical application of embolization in trauma patients and factors associated with a prolonged procedure time. Methods: Medical records of 162 trauma patients who underwent embolization between January 2007 and December 2020 at a regional trauma care center were reviewed retrospectively. Patients were divided into four embolized body regions: chest, abdomen, pelvis, and other. Patient demographics, trauma mechanism, physiology, trauma severity, embolization procedures, and 30‐day mortality were examined. The outcomes were identifying an embolized body region, embolized arteries, and procedure time. Multiple regression model was created to investigate the factors associated with prolonged procedural time in embolization. Results: Embolization was mainly undertaken in pelvic fractures ( n  = 96, 59%) and abdominal organ injuries ( n  = 57, 35%) and extended to the chest ( n  = 17, 10%), and other ( n  = 20, 12%). Approximately 13% ( n  = 21) of patients underwent embolization in two or more regions. Embolization was more strictly performed in minor artery injuries, for example, external iliac ( n  = 15, 16%) and lumbar artery ( n  = 22, 23%) branches in pelvic fractures, and inferior phrenic artery ( n  = 2, 3.5%) branches in liver injuries. Multiple regression model indicated that the number of embolized arteries ( P  = 0.021) and number of embolized regions ( P  < 0.001) were associated with prolonged procedural time in embolization. Conclusions: Embolization for trauma patients extended to various trauma regions. In time‐sensitive embolization, emergency interventional radiologists showed superior knowledge of expected embolizing arteries and factors associated with procedure time. Abstract : Embolizations for trauma patients extended to various trauma regions. Emergency interventional radiologists had better know expected embolizing arteries and factors associated with prolonged procedure time to achieve time‐sensitive embolization.